EEG Research Based on the Influence of Different Music Effects. (September 2020) - Xu, Yanjun; Xu, Xin; Deng, Lixin
Abstract: Music has become one of the methods for regulating emotions in the daily life of most people. Different concerts bring different emotional changes to people, but the effect of music on the changes of human brain and EEG signals is little known. This paper uses the brain wave (EEG) experiment to study the effect of different musical stimuli on attention, and focuses on comparing the effects of brain wave music and heavy metal music that are widely studied on attention. In this paper, an experiment was designed to collect the EEG signals of 15 students in three states: brainwave music (slow 80BPM), heavy metal music (fast 140BPM) and resting EEG signals. Independent component analysis (ICA) preprocesses the EEG signal, and uses T, T, and T to analyze the characteristics of the α, β and θ wave signals obtained by wavelet transform. Through the experimental analysis of this article, it is found that brain wave music has a significant effect on the alpha wave (P<0.05), and heavy metal concerts have an effect on the power value of the beta wave. The experimental results show that brain wave music, which is the slow board music, can better pay attention. The concentration of force, and heavy metal music (clapper music) will make the attention more distracting.